Design of heterogeneous data integration platform of smart mine - YANG Shaohua; ZHOU Xin; BI Junlei (Gong-kuang zidonghua, 2015)
In view of problem of heterogeneous data source existed in current information system in the process of smart mine construction, a solution was presented that uses XML technology to establish heterogeneous data integration platform, overall framework of the smart mine and architecture of the heterogeneous data integration platform were introduced. Under the condition of without changing physical location and system structure of existing data sources, the platform uses XML technology to losslessly convert heterogeneous data to XML documents, and realizes effective integration of heterogeneous data sources through analysis, decomposition and conversion of application demand of smart mine safety production decision. The platform provides data support for monitoring, management and decision-making of smart mine.